Analysis of retaining wall using Eurocode and British Standard - Nor Zalina Zakaria (School of Environmental Engineering, University Malaysia Perlis, 2013)
This program was focused on the analysis of the design; this design is based on BS 8110 and Eurocode 2 using Microsoft Excel. This program is designed to simplify the design process and reduce errors compared to manual designs. Results of this study were used to determine the appropriate type and the differences weather it designed using British Standard or Eurocode.